Obstructive sleep apnea treatment with dental appliance - Rubens Reimão; Marcia Maria de Gouveia; Maria da Conceição de Gouveia Pestana; Sandra Regina Lopes; Élio Giacomo Papaiz; Luiz Fernando Papaiz (Arquivos de Neuro-Psiquiatria)
The case of a 40-year-old male patient with obstructive sleep apnea syndrome (OSAS) is reported, with emphasis on treatment with a dental appliance. This therapeutic approach, which has been focused on recent research, has as its objective, the posturing of the mandibule and, consequently, the tongue more anteriorly, thus in turn leading to an increase in the posterior oropharyngeal airway space (PAS). Cephalometry contributed determining in this case whereby enlargement limits were observed in the PAS with mandibular displacement. Clinical and polysomnographic controls showed subjective reduction of the excessive daytime sleepiness and objective decrease in apneas intensity to normal limits. Eight months follow-up evidenced the steady improvement.